The Productivity of Gillnet Mesh Size as A Substitute for Cantrang in Tamasaju Village, North Galesong District, Takalar Regency - Abdalia rusdi; Sri Suro Adhawati; Najamuddin; Sutinah Made; Hamzah; Aris Baso (Hasanuddin University, 2022)
The objective of this research was to determine the efficiency and productivity of gillnet mesh size in North Galesong District, Takalar Regency. The type of research was survey research with a quantitative descriptive approach to obtain a sample from a population that describes or explains catch production, productivity, and efficiency of gillnet fishing gear. The population of this research was 40 cantrang fishermen who switch to using gillnet fishing gear in North Galesong District. The sample was all cantrang fishermen who switched to gillnet fishing gear. The sampling method employed in this study was a census sampling strategy, where all members of the population were used as samples. The methods of data collection were questionnaires, observations, and interviews. The results showed that the most efficient gillnet mesh size of the five mesh sizes 1 inch, 1.5 inch, 2 inch, 2.5 inch and 6 inch is the 1.5 inch mesh size with a value of 3.90. The results of the calculation of the productivity of gillnet fishermen in each mesh size has a different value. The highest gillnet productivity was at 1 inch mesh size with a value of 44.40kg/trip, then the lowest productivity was at 2.5 inch mesh size, which was 24.39 kg/trip.